2011 International Design Exchange Project, Hidden Space Project. Volume 2, Urban rooftops - Newman, Kaye; Harris, Janette; Park, Young Tae; Kim, Hong Ki; Kim, Suk Young (Total Design, 2011)
Urban Rooftops: Our cities are now having to rethink and redevelop the use of space more creatively and ingeniously than ever before. Space is precious in any context but the extra pressure cities’ face with the ever growing need to accommodate increasing populations mean that every open area is now a new possibility for spatial development.